Physicochemical and functional optimization of probiotic yogurt with encapsulated Lacticaseibacillus paracasei E1 enriched with green tea using Box–Behnken design - Muhaimin Rifa'i; Mochammad Fitri Atho'illah; Siti Nur Arifah; Aditya Ragil Suharto; Aghnia Nuri Fadhilla; Nur Alfi Maghfirotus Sa'adah; Esha Ardiansyah; Rahmi Izati; Belinda Nabiila Al Faizah; Dawama Nur Fadlilah; Septhyanti Aprilia Kavitarna; Shinta Oktya Wardhani; et al. (Applied Food Research)
Probiotic dietary supplements are in demand worldwide due to consumer awareness of healthy diets. However, it is still challenging to develop a functional yogurt by enriching it with a natural product. Green tea (GT) has many positive impacts on health and greater flexibility when mixed in various systems without losing its antioxidant properties. The objective was to evaluate the concentrations of GT and encapsulated Lacticaseibacillus paracasei E1 (LpE1) and its incubation time using Box–Behnken Design (BBD) for developing functional food with better characteristics and rich antioxidants. LpE1 beads were prepared by extrusion, visualized using SEM, and characterized by FT-IR. The BBD was set with three independent variables: GT (2‒4 % w/v), encapsulated LpE1 (2‒4 % w/v), and incubation time (18‒30 h). Our findings demonstrated that LpE1 beads have spherical shapes with 1.89 ± 0.03 mm in size. FTIR demonstrated that chemical interaction between LpE1 and biopolymer functional groups has a minor effect on the LpE1 bead structure. The optimum conditions by RSM with 81 % desirability values were 4 % GT, 2 % encapsulated LpE1, and a 30-h incubation time, resulting in 4.15 pH, 76.28 % WHC, 23.72 % syneresis, 16.49 cP viscosity, 13.67 color (ΔE), 89.84 % DPPH, 380.51 mg GAE/g TPC, and 802.65 mg QE/g TFC. The titratable acidity and viability were 1.39 % and 9.55 log CFU/mL, respectively. A 4 % GT addition reduced the acceptance rate of GT yogurt (GTY) than plain yogurt (PY). Incorporating GTY with encapsulated LpE1 might be promising to improve the physicochemical properties and functional values of yogurt.